Research on the Influence of Tolerance of Opportunistic Behaviors of Channel Boundaries on the Choice of Response Strategies - Chen, Jinsong; Liu, Zhaoxia; Hu, Ruoqian (Frontiers in Psychology, 2022)
In Chinese human society, border agents in channel transactions will choose different opportunistic behaviour response strategies to the tolerance of other members based on the relationship between the two parties. Based on 206 valid questionnaires collected, structural equation model (SEM) and regression analysis were used to investigate the influence of opportunistic behaviour tolerance on response strategy selection. The results show that the channel boundary personnel's tolerance to opportunistic behaviour (based on work or personal) negatively influence their choice of positive response strategy and a positive influence on their choice of the negative response strategy. Among the mediating effects of contract making, the contract terms positively promote the work-based and individual-based negative response strategies but have no mediating effect on the work-based and individual-based positive response strategies.